2022
DOI: 10.1371/journal.pone.0269559
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of azo dyes by a novel aerobic bacterial strain Bacillus cereus strain ROC

Abstract: Synthetic dyes are widely used as colorant compounds in various industries for different purposes. Among all the dyestuffs, azo dyes constitute the largest and the most used class of dyes. These dyes and their intermediate products are common contaminants of ground water and soil in developing countries. Biological methods have been found to be promising for the treatment and degradation of these compounds. In the present study, we focused on the biological removal of azo dyes (Reactive orange 16 and Reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In particular, most of the studies were carried out in bioreactors and used stirring to distribute the cells and the dye well. For example, Fareed et al shows that temperature can have a strong influence on the degradation efficiency of Bacillus cereus on reactive dyes (Fareed et al 2022). They showed that the decolorization efficiency was at 100% at 37 °C compared to 40% at 30 °C for 100 mg l −1 of RO-16.…”
Section: Comparison With Literature Datamentioning
confidence: 99%
“…In particular, most of the studies were carried out in bioreactors and used stirring to distribute the cells and the dye well. For example, Fareed et al shows that temperature can have a strong influence on the degradation efficiency of Bacillus cereus on reactive dyes (Fareed et al 2022). They showed that the decolorization efficiency was at 100% at 37 °C compared to 40% at 30 °C for 100 mg l −1 of RO-16.…”
Section: Comparison With Literature Datamentioning
confidence: 99%
“…All the group of samples were subjected for incubation in triplicates in similar environmental setups. After seven days, the germination rate and the size of the shoot and root were measured [22] [23] [24] [25] [26].…”
Section: Phytotoxicity Assessmentmentioning
confidence: 99%
“…In one investigation, Louati et al [102], found 100% decolorization of dyes at pH 8 by using Pseudomonas aeruginosa strain Gb30, whereas Montanez-Barragan et al [103] observed above 90% decolorization of dyes at pH 6-11 with Halomonas species. Another researcher, Shi et al [104], found 100% dye removal of Brilliant Crocein by using the bacteria Providencia rettgeri, while Fareed et al [105] found 80-100% decolorization of dyes by using free and immobilized cells of Bacillus cereus at temperatures of 32 [107] observed the complete decolorization of malachite green and crystal violet at pH 3-10 and a temperature of 20-45 • C after 12 h of incubation under optimal environmental conditions using Serratia species, which is a new bacterial strain identified via 16S rDNA analysis. In a recent study, Tripathi et al [10] observed 98% dye decolorization of crystal violet dye using a native multiple metal-tolerant Aeromonas caviae MT-1 isolate.…”
Section: Pure Bacterial Culturesmentioning
confidence: 99%